Ages and Abilities : The Stages of Childhood and their Social Recognition in Prehistoric Europe and Beyond - Rebay-Salisbury, Katharina (Archaeopress Publishing, 2022)
This volume explores social responses to stages of childhood from the late Neolithic to Classical Antiquity in Central Europe and the Mediterranean. Comparing osteological and archaeological evidence, as well as integrating images and texts, authors consider whether childhood age classes are archaeologically recognizable.